Novel genomic variants influencing methotrexate delayed clearance in pediatric patients with acute lymphoblastic leukemia - Choi, Jung Yoon; Kwon, Hoshik; Kim, Hyery; Hong, Kyung Taek; Ma, Youngeun; Koh, Kyung-Nam; Yun, Sunmin; Yoo, Keon Hee; Song, Sang Hoon; Im, Ho Joon; Kim, Ju Han; Kang, Hyoung Jin (Frontiers in Pharmacology, 2024)
Background: Methotrexate (MTX) is the primary drug used in the treatment of pediatric acute lymphoblastic leukemia (ALL). However, some patients exhibit delayed clearance of high-dose (HD) MTX, which induces severe nephrotoxicity, mucositis, hepatotoxicity, and neurotoxicity. We sought to identify relevant variants associated with delayed clearance of HD-MTX in pediatric patients with ALL.Methods: Whole-exome sequencing of germline DNA was performed in 51 Korean pediatric patients with ALL. A total of 341 HD-MTX infusion data points from 51 patients were analyzed. MTX levels and laboratory measurements reflecting toxicity outcomes were obtained. Correlations between peak serum MTX levels at 24 h and toxicity outcomes were assessed. Analyses were performed to identify variants affecting delayed MTX clearance.The 24 h MTX level strongly correlated with the subsequent creatinine (Cr) level. Moreover, rs2229866 in contactin 2 (CNTN2), rs200687372 in myotubularin Related Protein 9 (MTMR9), rs777260512 in polymerase iota (POLI), rs16954698 in polycystic kidney disease 1-like 2 (PKD1L2), rs117765468 in NSE1 Homolog, SMC5-SMC6 Complex Component (NSMCE1), and rs1800956 in endoglin (ENG) were identified as candidate variants associated with delayed MTX clearance. In particular, ENG rs1800956 was significantly associated with delayed MTX clearance in all analyses and PKD1L2 rs16954698 was replicated in an external dataset (phs000637.v1.p1) from the Database of Genotypes and Phenotypes (dbGaP).Conclusions: This is the first whole-exome sequencing-based analysis of delayed MTX clearance in pediatric patients with ALL. ENG rs1800956 and PKD1L2 rs16954698 were found to be potentially influential variants associated with delayed MTX clearance. These findings provide insights into HD-MTX-induced nephrotoxicity and may contribute to adverse reactions by treatment modification.